Analyze the rear suspension structure for passenger car - Abdul Hadi, Abdul Aziz (2007)
The design of vehicle, suspension system is very important. The suspension system is including of the spring and the absorber. Suspension system is very important in optimum the driving in term of comfort and safety. Furthermore, it is important to identify the suitable suspension for the cars. Because of that the research is done in order to analyze the effect of number of coils to the stiffness and the forces require tending back the spring to the original position. In order to find the stiffness of the spring, manual calculation will be use. After the stiffness got, the value will be use in simulation which is cosmos motion software. Each coil has different values of stiffness. From simulation the different value of force will be get because of each spring with different coil will have different value of force. The analysis is done to identify the effect of the number of coils to the spring. With the different number of coils the stiffness of spring will be different and this research wants to identify whether the value of stiffness will increase or decrease due to different of coils. In this research the suspension of Proton Waja will be use because of the passenger car. The load that will be given in the simulation is 2000N, 3000N and 4000N. The numbers of coils that will be analyzed are 6 coils, 7 coils, 8 coils and 9 coils. The final results from calculation and simulation will be comparing according to the number of coils.